Analisis Status Hak Waris Anak Di Luar Nikah Menurut Kompilasi Hukum Islam - Meita Djohan OE (KEADILAN PROGRESIF, 2015)
One of the problems existing inheritance law in Indonesia is about to marry the child outside the legal compilation of Islamic law. Problems in this writing how state inheritance rights of children outside of marriage according to Islamic law compilation method used is a normative juridical approach, data sources obtained from the literature. Data collected by literature study further in qualitative analysis. Based on the results of this study pointed out that the status of the inheritance rights of illegitimate children according to Islamic law compilation is that the child is only entitled to inherit from his mother and his mother's family. against the biological father of the child did not give rise to a relationship of mutual inherit. Suggestions are expected for regulators especially in compilation of Islamic law was made stricter regulations in order to get legal certainty on the part of his legacy.